2017
DOI: 10.1002/sctm.15-0327
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of Maternal Cell Contamination and Overgrowth in Isolating Fetal Chorionic Villi Mesenchymal Stem Cells from Human Term Placenta

Abstract: Human placenta is rich in mesenchymal stem/stromal cells (MSC), with their origin widely presumed fetal. Cultured placental MSCs are confounded by a high frequency of maternal cell contamination. Our recent systematic review concluded that only a small minority of placental MSC publications report fetal/maternal origin, and failed to discern a specific methodology for isolation of fetal MSC from term villi. We determined isolation conditions to yield fetal and separately maternal MSC during ex vivo expansion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…CVC exhibit a delayed replicative senescence and maintenance of telomere length; however, variations in isolation techniques may lead to varying degrees of contamination with maternal cells. 53 In fact, our study illustrates that different isolates from the same layer may have dissimilar characteristics as noted by the distinct sets of data derived from CSC and CVC for AKT and MMP-2 activation. As we did not sequence these isolates, we are unable to speculate on the potential differences between them.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…CVC exhibit a delayed replicative senescence and maintenance of telomere length; however, variations in isolation techniques may lead to varying degrees of contamination with maternal cells. 53 In fact, our study illustrates that different isolates from the same layer may have dissimilar characteristics as noted by the distinct sets of data derived from CSC and CVC for AKT and MMP-2 activation. As we did not sequence these isolates, we are unable to speculate on the potential differences between them.…”
Section: Discussionmentioning
confidence: 66%
“…Although isolation of MSC derived from placental layers including from whole chorion and chorionic villi 27,49–52 has been reported, there are few if any current clinical trials utilizing this source of MSC. CVC exhibit a delayed replicative senescence and maintenance of telomere length; however, variations in isolation techniques may lead to varying degrees of contamination with maternal cells 53 . In fact, our study illustrates that different isolates from the same layer may have dissimilar characteristics as noted by the distinct sets of data derived from CSC and CVC for AKT and MMP‐2 activation.…”
Section: Discussionmentioning
confidence: 77%
“…Both fPL‐MSC and fBM‐MSCs satisfied the International Society for Cellular Therapy (ISCT) specification of human MSC characterization. MSCs appeared as plastic‐adherent spindle‐shaped cells in culture and differentiated adequately along the osteogenic and adipogenic lineages . Both MSCs had the appropriate cell surface markers expression (Figure S1A and B, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical strategy for cell therapies was based on replacement by differentiation of grafted MSCs or stem cells of dead neurons, but many studies showed that cell therapies promote regeneration and repair of damaged tissue due to stroke, including angiogenesis, neurogenesis, and axonal outgrowth, together with regulating corresponding molecular cascades [32]. Although the approach with these cell therapies was shown to be safe, and they passed through the BBB and reached injured tissues [50], one cannot exclude the possibility of complications after grafting cells, such as cell rejection, unpredictable immune responses, possible contamination, problems of storage of cells before their use, and inducing tumor formation [51][52][53][54]. Exosomes offer an advantage to overcome the limitations of cell therapy, such as: (1) less tumorigenicity due to their to inability to self-replicate; (2) dosing not affected by loss of transplanted cell viability; (3) not occluding the microvascular system; (4) tough lipid bilayer vesicles that can be easily stored for a long time at −80 • C and other extremes of handling, while retaining bioactivity; (5) their low immunogenicity not requiring a host immune response and a match between the donor and the recipient; (6) capable of extracting sufficient amounts from immortalized stem cells; and (7) capable of enhancing efficacy by genetic engineering of the parent cells [44,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%